2010
DOI: 10.1039/b926368n
|View full text |Cite
|
Sign up to set email alerts
|

Controlled vapor-phase synthesis of cobalt oxide nanomaterials with tuned composition and spatial organization

Abstract: Cobalt oxide nanostructures are deposited by Chemical Vapor Deposition (CVD) on Si(100) substrates\ud at temperatures between 300 and 550 °C, using for the first time a novel Co(II) adduct as molecular\ud precursor [Co(hfa)2 TMEDA; hfa =1,1,1,5,5,5-hexafluoro-2,4-pentanedionate, TMEDA= N,N,N0,N0-tetramethylethylenediamine]. The preparation is conducted either under dry (O2) or wet (O2\ud + H2O) oxygen atmospheres, at total pressures of 3.0 or 10.0 mbar. The obtained results evidence that,\ud upon dry O2 at 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
116
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 68 publications
15
116
0
Order By: Relevance
“…Thanks to the Co 3 O 4 bandgap, which is lower than 2.0 eV, [ 117 ] UV irradiation can easily promote the formation of e − CB − h + VB pairs, the direct actors of the subsequent photo reforming process. Operation in the absence of oxygen may lead to a partial Co 3 O 4 reduction to CoO, resulting in a performance deterioration [ 82 ] as well as to poisoning of the photo catalyst surface by methoxy species resulting from CH 3 OH adsorption and partial photodecomposition.…”
Section: Photocatalytic Hydrogen Productionmentioning
confidence: 99%
“…Thanks to the Co 3 O 4 bandgap, which is lower than 2.0 eV, [ 117 ] UV irradiation can easily promote the formation of e − CB − h + VB pairs, the direct actors of the subsequent photo reforming process. Operation in the absence of oxygen may lead to a partial Co 3 O 4 reduction to CoO, resulting in a performance deterioration [ 82 ] as well as to poisoning of the photo catalyst surface by methoxy species resulting from CH 3 OH adsorption and partial photodecomposition.…”
Section: Photocatalytic Hydrogen Productionmentioning
confidence: 99%
“…The features of a broadening of the main component and a shake-up satellite are indicative of high-spin Co 2+ species in the bilayer structure [16][17][18] (as also predicted by DFT calculations 11 ). On the other hand, low-spin Co 3+ compounds exhibit almost no satellite structure 19 . These observations point to the cobalt being either completely or partially in the low-spin Co 3+ state in both of the trilayer and multilayer structures, reflecting the higher coordination to O.…”
Section: Xps and Valence Band Spectroscopymentioning
confidence: 99%
“…3 4 It has been widely demonstrated that this problem can be partly solved via constructing nanostructured electrode materials because of better accommodation of the strains of Li-ion insertion/ desertion than in micrometer-scale materials. [12][13][14][15][16][17][18][19][20][21][22][23] Especially, constructing one-dimensional (1D) nanostructured anodes is more effective solution against the volume change problem, because the nanowires or nanorods were not pulverized or broken due to facile strain relaxation of the nanowire geometry. [24][25][26][27][28] Very recently, self-supported 1D Co 3 O 4 nanostructure arrays on titanium and copper foils have been reported to have enhanced electrochemical performances and can conquer the drawbacks mixing with conductive carbon or polymers.…”
Section: Introductionmentioning
confidence: 99%